Termite assemblage collapse along a land-use intensification gradient in lowland central Sumatra, Indonesia - Jones, D.T.; Susilo, F.X.; Bignell, D.E.; Hardiwinoto, S.; Gillison, A.N. (2003)
Termites are major decomposers in tropical regions and play an important role in soil processes. This study measured the impact of land-use intensification on the termite assemblage of lowland rain fores in Jambi Province, on the Indonesian island of Sumatra. Termite composition was assessed in seven land-use types along a disturbance gradient, from primary forest, through different silvicultural systems, to grassland and cultivated land without trees. A range of environmental variables was also measured. Comparisons with other studies show that the decline in termite species richness and relative abundance seen at Jambi is a general trend that occurs elsewhere when forests are converted to other land uses. To help mitigate the loss of termites when forests are disturbed, the authors recommend the following management practices: the use of reduced impact logging techniques, maximising forest patch size and connectivity, minimizing length of forest edges, and leaving dead wood to decay in situ.